Evaluasi Layanan Inovasi Program ARTIS (Antar Gratis) di Kecamatan Gedangan Kabupaten Sidoarjo - Aulia Dwi Aristawati (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to evaluate the innovation of the ARTIS (Free Delivery) Program in Gedangan District, Sidoarjo Regency. The ARTIS Program is a service that delivers administrative documents (such as ID cards, family cards, and birth certificates) directly to recipients' addresses free of charge, as a solution to the problem faced by people who are unable to collect physical documents from the district office during working hours. This program utilizes collaboration with the private sector, namely J&T Express. Using a descriptive qualitative evaluative research method with six evaluation indicators from William N. Dunn (Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy), this study found that the ARTIS Program has had a positive impact overall. The program is considered effective because it makes things easier for the community and efficient because it utilizes existing resources. In addition, the program's Responsiveness and Accuracy are very strong because they are in line with the needs of urban communities for fast, easy, and inclusive services. However, the Adequacy aspect is still limited due to the number of vehicles and types of documents served, and Equity requires the expansion of socialization to the neighborhood/community association (RT/RW) level to ensure equal access to information for all residents. Improvements are needed, particularly through the development of digital systems and increased service capacity, to make this program more effective, measurable, and sustainable.